Simulating Contestability in Freight Transportation: The Canadian Grain Handling and Transportation System. (1st October 2016) - Lawrence, R.; Nolan, J.; Schoney, R.
Modern supply chains are characterised by multiple interactions among individuals and evolving temporal patterns of interaction. The grain handling and transportation system (GHTS) in Canada is a good example of a large modern supply chain. In this paper, we develop an agent-based simulation model of this regional supply chain, and use the simulation output to assess the viability of an open-rail access policy designed to mitigate railway market power in the system. We find that if open-rail access in the Canadian GHTS were to be implemented, profitable entry opportunities would, at best, be very limited.